The Geopolitics of the Poles and their Neighbors in the Works of Fedor Dostoevsky - Мария Михновец (Polilog: Studia Neofilologiczne, 2020)
The article is devoted to the study of the place of Poland and Poles on the geopolitical map in Dostoevsky’s picture of the world. The artistic and journalistic heritage of the writer is analyzed in terms of what other countries and peoples are mentioned in its connection with Poland and Poles. That allows to determine Dostoevsky’s geopolitical orientations both in relation to Poland and the Russian Empire. In Dostoevsky’s picture of the world Poles like Jews are not anchored and have a marginal position among other peoples of the Russian Empire. For Dostoevsky Poland is on a borderline between the Slavic world and Europe, which is actualized through the close relationship of the Poles with the French. The connection with the other European nations is optional, with the exception of the Western Slavs: the Czechs and the Serbs.